2007
DOI: 10.1073/pnas.0700664104
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and survival induced by Toll-like receptors is antagonized by type I IFNs

Abstract: TRIF is an adaptor protein associated with the signaling by Toll-like receptor (TLR)3 and TLR4 for the induction of type I IFNs. Here, we demonstrate a mechanism by which TLR signaling controls cell proliferation and survival. We show that TLR3 and TLR4 can induce cell cycle entry via TRIF, which targets the cell cycle inhibitor p27 kip1 for relocalization, phosphorylation by cyclin/cdk complexes, and proteasome degradation. These events are antagonized by type I IFN induced by the TRIF pathway. Furthermore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 51 publications
10
67
0
Order By: Relevance
“…The present data support a switching function of type I IFN in the functional outcome of TLR triggering in tumor cells, as it has been recently shown in DC (37). Indeed, TLR3 triggering induces NF-B activation in tumor cells regardless of their fate, but only cells producing IFN-␣ through the p38 MAPK pathway are induced into apoptosis.…”
Section: Discussionsupporting
confidence: 65%
“…The present data support a switching function of type I IFN in the functional outcome of TLR triggering in tumor cells, as it has been recently shown in DC (37). Indeed, TLR3 triggering induces NF-B activation in tumor cells regardless of their fate, but only cells producing IFN-␣ through the p38 MAPK pathway are induced into apoptosis.…”
Section: Discussionsupporting
confidence: 65%
“…In fact, TBK1 has been reported to promote tumor growth and proliferation of HUVECs (27). Hasan et al (28) reported that TRIF/TBK1 regulates phosphorylation of the cell cycle inhibitor p27 kip1 and proteasome degradation. Because phosphorylation of p27 can be induced by Akt (29), our results suggest that TRIF/TBK1-induced phosphorylation and degradation of p27 is at least partly mediated by Akt after it is activated by TBK1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IKKα can reduce overall p27 levels independent of IFN signaling and the TLR-NFκB signaling pathway may represent an additional TLR-mediated pathway involved in regulating cell cycle entry and exit. 37 Therefore, because IKKα is a known regulator of 14-3-3σ, it is possible that IRF6, 14-3-3σ, and IKKα function through similar pathways, perhaps in coordination with TLR3 signaling, to regulate specific cell cycle events that are necessary for exit from the cell cycle and entry into the G(0) differentiation phase.…”
Section: Irf6 As a Transcription Factormentioning
confidence: 99%
“…34,35 Work by Hasan and colleagues has suggested that signaling through TLR3 and TLR4 following stimulation with their respective ligands polyI:C (a synthetic double stranded RNA) and lipopolysaccharide (LPS) can induce entry into the cell cycle, but only in the absence of type I IFN signaling, which is also regulated through TLR signaling pathways. 36,37 Because IRFs are known regulators of type I IFN, it is possible that IRF6 functions through canonical TLR-IRF signaling pathways to induce type I IFN as a means of promoting quiescence and differentiation.…”
Section: Irf6 As a Transcription Factormentioning
confidence: 99%